Sustainable supply chain management capabilities: a review from the resource-based view, the dynamic capabilities and stakeholder theories (2014)
A semi-structured literature review was performed to understand sustainable supply chain management (SSCM) capabilities mainly from the perspectives of the resource-based view of the firm, dynamic capabilities view and stakeholder theory, including exploring their nature, origins and effects on firm performance. The capabilities construct remains scarce in the SSCM literature and literature reviews are almost non-existent. Particularly, the dynamic capability construct has barely been applied in the SSCM field. The nature of most SSCM capabilities studied to date is static and needs the support of organisational antecedents like supply management capabilities, strategic purchasing and corporate social and environmental proactivity, and is likely to positively impact firm performance. SSCM capabilities appear to be triggered not only by diverse pressures from external stakeholders, industry and markets, but also by internal factors independent of external sources.